2005
DOI: 10.1007/s00467-005-1970-1
|View full text |Cite
|
Sign up to set email alerts
|

Zero balance ultrafiltration (Z-BUF) in blood-primed CRRT circuits achieves electrolyte and acid-base homeostasis prior to patient connection

Abstract: Infants requiring CRRT present a unique challenge due to the large circuit volume to blood volume ratio. Blood priming is often used, but some patients can become unstable during the initiation of CRRT due to electrolyte and acid-base imbalance. We postulated that using Z-BUF we could normalize electrolytes and improve the acid base status of the prime prior to patient connection. To test this we set up a circuit using the Baxter BM-25 CRRT pump, a polysulfone or AN-69 membrane, and a three-way stopcock. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Manipulation of the bloodprimed circuit before connection to the patient is often necessary. Either the zero-balance ultrafiltration technique, which results in buffered blood priming, 30 or the circuit bypass method, which avoids initial contact of the acidotic donated red blood cells with the AN-69 membrane can be used. 28 Compared with traditional blood priming methods, the circuit-to-circuit exchange technique takes place over 3 to 5 minutes, thereby reducing the risk of fluid accumulation and reduced solute clearance associated with prolonged interruptions of CRRT.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of the bloodprimed circuit before connection to the patient is often necessary. Either the zero-balance ultrafiltration technique, which results in buffered blood priming, 30 or the circuit bypass method, which avoids initial contact of the acidotic donated red blood cells with the AN-69 membrane can be used. 28 Compared with traditional blood priming methods, the circuit-to-circuit exchange technique takes place over 3 to 5 minutes, thereby reducing the risk of fluid accumulation and reduced solute clearance associated with prolonged interruptions of CRRT.…”
Section: Discussionmentioning
confidence: 99%
“…While centrifugal cell washing as of 2004 was used in 60% of congenital heart surgery centers (16) and has been shown to be effective in correcting pH and lowering potassium, lactate and glucose (17)(18)(19), several studies have reported that the process increases cell wall fragility and leads to increased hemolysis (20)(21)(22). Blood prime ultrafiltration has also been reported to make the prime physiologic, but without the attendant hemolysis or additional disposables cost (23)(24)(25)(26).…”
Section: The Need and Problems Of Rbc Transfusion During Neonatal Carmentioning
confidence: 99%
“…However, packed RBCs have frequently abnormal electrolyte and acid-base balance, which are used for blood priming [12]. Therefore, the mixed fluid, which primed the circuit, should be purified before connecting to neonates, and the carrying out of blood priming takes up to 30 min more [6,12]. In addition, the frequent use of packed RBCs would increase the risk of transfusion-associated complications, such as various infections [24,25].…”
Section: Blood Primingmentioning
confidence: 99%
“…However, packed RBCs have frequently abnormal electrolyte and acid-base balance, which are used for blood priming [12]. Therefore, the mixed fluid, which primed the circuit, should be purified before connecting to neonates, and the carrying out of blood priming takes up to 30 min more [6,12].…”
Section: Blood Primingmentioning
confidence: 99%
See 1 more Smart Citation